Differences in Student Bullying Behavior in terms of Gender and Cultural Background - Reka Arya Purnama Sari; Yeni Karneli (Universitas Negeri Padang, 2020)
Bullying is a form of intimidation carried out by strong parties against those who are physically, verbally and mentally weak and can be identified through forms of physical violence, verbal violence and psychological violence. Bullying has a great opportunity to be imitated because this negative behavior is mostly done by students. Bullying behavior is not only done by male students but female students also bullying. This study aims to describe differences in student bullying behavior in terms of gender. Bullying behavior is based on several aspects (1) physical bullying (2) verbal bullying (3) mental or psychological bullying. The hypothesis proposed is that there is a significant difference in bullying behavior between male and female students. This type of research is quantitative with a descriptive-comporative approach. The sample in this study amounted to 81 students, who were students of class XI and XII SMA Pertiwi 1 Padang. The sampling technique used in this study was proportional random sampling. The research instrument was a bullying behavior questionnaire. The data were processed using descriptive statistical analysis techniques and analysis of different tests (t-test). The results revealed: (1) the bullying behavior of students of SMA Pertiwi 1 Padang was in the low category with a percentage of 41%, (2) there was a significant difference between student bullying behavior in terms of gender and cultural background. Based on the research findings, it is suggested that guidance and counseling teachers be able to provide guidance and counseling services in the form of information services, individual counseling, group guidance services and group counseling services that reduce bullying in students.